2008
DOI: 10.1021/jp711039s
|View full text |Cite
|
Sign up to set email alerts
|

Individually Dispersing Single-Walled Carbon Nanotubes with Novel Neutral pH Water-Soluble Chitosan Derivatives

Abstract: Chitosan and its various neutral pH water-soluble derivatives were investigated for dispersing single-walled carbon nanotubes (SWNTs). Chitosan (CS) can produce good dispersion of SWNTs, but only in acidic pH condition. Our two novel derivatives, O-carboxymethylchitosan (OC) and OC modified by poly(ethylene glycol) at the −COOH position (OPEG), were able to produce highly effective debundling and dispersion of SWNTs in neutral pH aqueous solution. Atomic force microscopy (AFM), transmission electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 55 publications
2
80
0
Order By: Relevance
“…The absorption bands in the wavelength range from 400 to 600 nm represent the lowest energy M 11 van Hove transition of metallic SWNTs, from 550 to 800 nm represent the second van Hove transition of semiconducting SWNTs (S 22 ) and from 800 to 1400 nm correspond to the first van Hove transition of semiconducting SWNTs (S 11 ). The S 11 peaks marked increase of intensity as they are easily affected by the SWNT chemical environment [35]. Fig.…”
Section: Characterization Of Swnt-nachi Dispersionmentioning
confidence: 94%
“…The absorption bands in the wavelength range from 400 to 600 nm represent the lowest energy M 11 van Hove transition of metallic SWNTs, from 550 to 800 nm represent the second van Hove transition of semiconducting SWNTs (S 22 ) and from 800 to 1400 nm correspond to the first van Hove transition of semiconducting SWNTs (S 11 ). The S 11 peaks marked increase of intensity as they are easily affected by the SWNT chemical environment [35]. Fig.…”
Section: Characterization Of Swnt-nachi Dispersionmentioning
confidence: 94%
“…10 Chitosan and its derivatives have been studied for its dispersing of CNTs in solvents. 11,12 On the other hand, the conformation of chitosans on CNTs is very important for the application of the CNT composite. 13,14 Though chitosan/CNTs systems have been extensively studied, little research is reported for the interaction of chitosans with CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1e shows a representative AFM image of nanotube network deposited on wafers. www.advmat.de www.MaterialsViews.com COMMUNICATION 96reported to be around 0.12 mg mL − 1 , [ 12 ] although when these solutions are further processed for purifi cation and separation, only a fraction of nanotubes compared to the starting solution are left in the resultant solution. In our experiments, we varied the nanotube concentration until just prior to precipitation, and also via dilution until no nanotubes were visibly deposited.…”
mentioning
confidence: 99%